Encyclopaedic visions : - Yeo, Richard R. (Cambridge University Press, 2001)
Encyclopaedic Visions provides a major contribution to Enlightenment studies, the history of science, and the history of ideas in general. Richard Yeo places these scientific dictionaries in a rich cultural framework of debate that includes the classification of knowledge, the tradition of commonplaces, the Republic of Letters, the Enlightenment public sphere, copyright issues, and the specialization of science.